Synthesis and characterization of thermoresponsive poly (N-vinylcaprolactam) / fillers nanocomposite - Mohammed, Marwah Noori (2019)
Poly (N-vinylcaprolactam) (PNVCL) has attracted much research attention recently as one of the promising thermoresponsive polymers. Even there is an essential factor that makes PNVCL very attractive; it has been reported that PNVCL needs to improve its mechanical characteristics, biocompatibility, and macroporosity to make it an exciting candidate for biomedical applications. Therefore, nanotechnology has been used as a way to enhanced PNVCL properties by adding a little amount of nanofiller while preserving the temperature-responsive properties. In this work, the significant parameters of polymerization have been identifying, then perform the synthesize and characterization of thermoresponsive polymer/fillers nanocomposites. A series of PNVCL nanocomposites were developed and incorporated with nanofillers (organoclay (C20) and maghemite multiwalled carbon nanotubes (Fe-MWCT)) via an in-situ polymerization process assisted by magnetic stirring. The synthesized PNVCL nanocomposites were subjected to different characterization processes such as thermal stability, conversion, morphology changes, swelling and rheological properties using different characterization methods like X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Nuclear magnetic resonance spectroscopy (NMR), and Scanning Electron Microscopy (SEM). The thermal stability of the nanocomposites was determined using Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC). From the results, the observed low and broad XRD peaks of the nanocomposites confirmed the lower angle regime of the samples due to the expansion of the basal spacing. An increase in the clay and Fe-MWCNTs content increased the d-spacing expansion of the nanocomposites. Additionally, the FTIR results show the mean absorption bands of the main functional groups in the nanocomposites such as hydrogen free carbonyl (C=O), hydrogen-bonded -OH stretching and free -OH stretching. Moreover, 1H and 13C NMR was used for polymer structure and degradation products characterization of the PNVCL nanocomposites. The TGA results show a significant improvement in the PNVCL nanocomposites after the incorporation of C20 and Fe-MWCNTs. The compatibility of Fe-MWCNTs with PNVCL was found to be higher compared to that of C20 in the polymer matrix. This was evidenced in the higher d-spacing, thermal, and mechanical properties of the nanocomposite formed with 0.3 wt% Fe-MWCNT compared to nanocomposite formed with 3 wt% C20. The intercalated structure of the PNVCL nanocomposites conferred improved thermal stability to the nanocomposites as determined by TGA. The DTG curves show no significant influence of higher C20 or Fe-MWCNT contents on the depolarization process, indicating a positive effect of the fillers on the thermal degradation process. The central composite design (CCD) of the response surface methodology (RSM) was employed during the optimization process in this study. The optimization process was performed with three process factors (temperature, time, and the amount of nanofillers) and the results show increases in the temperature and nanofillers content to favor the polymerization of the nanocomposites to a certain extent. The quadratic model developed was reasonably accurate. The insignificant lack of fit and low percentage errors during the validation experiment showed the validity of the optimization processes at a significant level for both nanocomposites.